MORF2-mediated plastidial retrograde signaling is involved in stress response and skotomorphogenesis beyond RNA editing - Yapa, Madhura M.; Doroodian, Paymon; Gao, Zhenyu; Yu, Peifeng; Hua, Zhihua (Frontiers in Plant Science, 2023)
Retrograde signaling modulates the expression of nuclear genome-encoded organelle proteins to adjust organelle function in response to environmental cues. MULTIPLE ORGANELLAR RNA EDITING FACTOR 2 (MORF2) was initially recognized as a plastidial RNA-editing factor but recently shown to interact with GUN1. Given the central role of GUN1 in chloroplast retrograde signaling and the unviable phenotype of morf2 mutants that is inconsistent with many viable mutants involved in RNA editing, we hypothesized that MORF2 has functions either dosage dependent or beyond RNA editing. Using an inducible Clustered Interspaced Short Palindromic Repeat interference (iCRISPRi) approach, we were able to reduce the MORF2 transcripts in a controlled manner. In addition to MORF2-dosage dependent RNA-editing errors, we discovered that reducing MORF2 by iCRISPRi stimulated the expression of stress responsive genes, triggered plastidial retrograde signaling, repressed ethylene signaling and skotomorphogenesis, and increased accumulation of hydrogen peroxide. These findings along with previous discoveries suggest that MORF2 is an effective regulator involved in plastidial metabolic pathways whose reduction can readily activate multiple retrograde signaling molecules possibly involving reactive oxygen species to adjust plant growth. In addition, our newly developed iCRISPRi approach provided a novel genetic tool for quantitative reverse genetics studies on hub genes in plants.